Pengembangan Sistem Manajemen Logistik dan Order di UBCOFFEE - Bayu Maulana Imran; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
UBCOFFEE is a coffee restaurant that has many variation of menus. Varitation of menus in a restaurant has a significant influence to consumer purchasing decision index. The more variety of menus available in a restaurant, the more the the restaurant needs efficiency in management of order and payment data. The restaurant needs a system that can support performance efficiency in logistic and order management. This application system will be built with Waterfall method of Software Development Life Cycle (SDLC) so that the system maintains quality during the development and maintenance process. The application system will be built with Flutter framework to make system more practical and executable by various platforms. This research begins with system design, then implemented into a program code that will be tested through white-box testing and usability testing by selected samples of testerwith System Usabilty Scale (SUS) as a standard. The test results of the system show that the logistics and order management system at UBCOFFEE has a usability scale with 72.63 points from the minimum point limit 68 in a scale between 1 and 100. It can be concluded that the system has met the usability standard.